A novel, transfemoral prosthesis designed to treat aortic valve regurgitation: technical aspects and procedural guide. Issue 12 (December 2019) - Russo, Marco; Werner, Paul; Moscato, Francesco; Rath, Claus; Stoiber, Martin; Hengstenberg, Christian; Andreas, Martin
Abstract : Supplemental Digital Content is available in the text